Liquefaction Potential Analysis Along Coastal Area of Bengkulu Province due to the 2007 Mw 8.6 Bengkulu Earthquake - Lindung Zalbuin Mase (Journal of Engineering and Technological Sciences, 2017)
This paper presents a seismic response analysis study of liquefiable sites along the northern parts of the coastal area of Bengkulu Province that underwent liquefaction phenomena during the strong earthquake (8.6 Mw) on 12 September 2007. Several investigation tests, including the standard penetration test (SPT) and the soil shear wave velocity test, were conducted at 8 locations. The data were used to simulate the seismic response in order to investigate soil behaviors during the earthquake. In addition, the excess pore water pressure ratio obtained from the analysis was compared with the prediction value calculated from empirical data. The results show that liquefaction can occur at shallow depth layers dominated by loose sand. The results also confirm field evidence collected during the earthquake that was reported in several previous studies. The excess pore water pressure ratio was in good agreement with the predicted value from the empirical approach.